Summary of the Experience in the Diagnosis and Treatment of Complex Preauricular Fistulas in 78 Children - Xu, Ying; Seng, Dongjie; Jiang, Lan; Wang, Shengcai; Ni, Xin; Zhang, Jie; Han, Fugen (Frontiers in Surgery, 2021)
Objective: This study aimed to investigate the application of mini-incisions in complex preauricular fistula resection in children. Methods: A total of 78 children who were diagnosed with preauricular fistula infection between January 2017 and December 2019 were included in the study. Their clinical data were analyzed retrospectively, and surgical treatment with mini-incisions based on plastic surgery principles and techniques was provided. Results: All the patients achieved healing following the first application of the treatment. The patients were followed up for 6–42 months, and no recurrence or local auricular deformation occurred. Conclusion: The application of mini-incisions and plastic surgery techniques in complex preauricular fistula resection in children can achieve a good effect and improve the satisfaction of the children and their parents.